Solidification–stabilization of organic and inorganic contaminants using portland cement: a literature review - Paria, Santanu; Yuet, Pak K (Environmental reviews, 2006)
The treatment of hazardous wastes using cement-based solidification–stabilization (S–S) is of increasing importance as an option for remediating contaminated sites. Indeed, among the various treatment techniques, S–S is one of the most widely used methods for treating inorganic wastes. To enhance the application of S–S and to further develop this technology for site remediation, particularly for organic contaminants, it is important to have a better understanding of the mechanisms involved in the process. The primary objective of this review is to survey the current knowledge in this subject, focusing on (i) cement chemistry, (ii) the effects of inorganic (heavy metals) and organic compounds on cement hydration, and (iii) the mechanisms of immobilization of different organic and inorganic compounds. For heavy metals, cement-based S–S technology has been shown to be effective in immobilizing the contaminants, even without any additives. In applying cement-based S–S for treating organic contaminants, the use of adsorbents such as organophilic clay and activated carbon, either as a pretreatment or as additives in the cement mix, can improve contaminant immobilization in the solidified–stabilized wastes. The concept of degradative solidification–stabilization, which combines chemical degradation with conventional solidification–stabilization, seems promising, although further study is required to assess its technical and economic feasibility.